(untitled) (AACINI - International Journal of Industrial Engineering, 2023)
The following work is mainly oriented to the operationalization, identification and decomposition of the theorical concept: university teaching performance, together with its respective dimensions; From a mathematical statistics point of view. For this theme, we ‘ve found the prevalence of the qualitative approach, with a focus on expert’s judgement. However, this doesn’t prevent the application of a quantitative criterion for the verification of a categoric system (1) That it’s trustworthy and reliable. As anticipated, this research, has a clearly quantitative approach, being the type of research design non-experimental; Mainly because we observe the behavior of the answers as they are given, without any manipulation. The analysis subjects were 31 students of the Industrial Engineering, who are currently studying as regular students at the UTN Regional Faculty Santa Cruz, In the context of a virtual classroom at the Moodle platform; During the period 2021-2022.It was implemented through a closed structured survey of 20 questions, using a Likert scale of 4 points (Uninteresting, Regular, Good, very interesting) in which we measured the concept: University teaching performance and its possible dimensions. In the study conducted, it was proposed to work on the operationalization of the variable under study and verify its validity and reliability. Based on the results achieved, the indicator that measures the university teaching performance is contrasted, in terms of validity and reliability, with similar analysis results and it is observed that it is within reasonable limits for the cases analyzed; we can make it a suitable indicator for research design.